Closed Reduction of an Isolated Zygomatic Arch Fracture Under Local Anesthesia: A Case Report - ATEŞ, OZAN (My University, 2024)
The zygomatic bone is one of the most prominent bones in the facial region. It forms the most anterolateral projection on each side of the middle face and is articulated with the maxilla, frontal, and temporal bones. Isolated zygomatic arch fractures can occur when a direct force is applied to the zygoma. A variety of intraoral and extraoral techniques have been used as closed reduction techniques for isolated fractures of the zygomatic arch. In this case report, we aim to present our approach for the treatment of a 40-year-old patient with an isolated right zygomatic arch fracture. We used the Keen technique for the closed reduction of the fracture under local anesthesia due to its practicality and effectiveness.
Keywords: ambulatory surgery; closed reduction; maxillofacial trauma; keen technique; isolated zygomatic arch fracture